Steel-concrete composite connections in a fire condition: a review (Revista Brasileira Multidisciplinar, 2025)
Steel-concrete composite connections are characterized by the fact that the concrete slab participates in the transmission of forces from a composite beam to a column or another composite beam in the adjacent span. Although there are composite connections with known and consolidated behavior, there are still doubts about the working mechanism of steel-concrete composite connections in a fire situation, in which high temperatures significantly alter the distribution of resistance and stiffness, both in the connections and in the elements associated with them. In this scenario, there is a shortage of worldwide research evaluating the behavior of steel-concrete composite connections in a fire situation. The objective of this work was to conduct a bibliometric analysis and subsequent systematic literature review about research on steel-concrete composite connections in fire situations, to outline the state of the art on the subject and contribute to the advancement of research in the area from the identification of the main gaps in existing knowledge. Among the identified gaps, the recommendations for conducting investigations on the behavior of steel-concrete composite connections stand out, considering their relationship with the structure globally, in addition to their isolated behavior.
Keywords: Steel-concrete composite structures; Composite connections; Fire; Bibliometric analysis; Systematic literature review.